Ответы и объяснения

Лучший Ответ!
2012-02-03T14:56:39+04:00

(a-b)(a+2) - (a+b)(a-2) = a^2+2a-ab-2b-a^2+2a-ab+2b=4a-2ab;

x^3 - (x^2-3x)(x+3) = x^3-x^3-3x^2+3x^2+9x= 9x.

В обеих примерах просто раскрываем скобки,и подобные слагаемые складываем. 

2012-02-03T15:54:11+04:00

(a-b)·(a+2)-(a+b)·(a-2)=                             2)x3-(x2-3x)*(x+3)

=(a²+2a-ab-2b)-(a²-2a+ab-2b)=                    =x3-((-1)x)(x+3)=

=a²+2a-ab-2b-a²+2a-ab+2b=                         =x3-(-1)x(x+3)=

=4a-2ab=                                                    =x3+1x(x+3)=

=-2ab+4a                                                    =x3+x(x+3)=

                                                                  =3x+x(x+3)=

                                                                   =3x+(x²+3x)=

                                                                    =3x+x²+3x=

                                                                    =6x+x²

                                                                     =x²+6x